WORLDS WITHIN A WORLD: INTERCULTURAL REPRESENTATIONS IN POLAND UNDER NAZI INFLUENCE (1939-1942) - Andrade, Nuno Neves (2012)
Europe, 1939. Germany, under the influence of the Nazi party, began a confrontation that shaped the face of the world. Firstly, the neighboring countries of Europe, then the farthest ones and even the African continent felt its force and trembled with fear. Fear, such a powerful feeling that, in small doses, can hone senses but, in large quantities can instill panic, suppress the intellectual capabilities and even destroy all that is held as true in each mind. Europe was a mix of several cultures; even countries were a mix of several cultures. Poland was one of these countries. In this country, Poles, Jews, Ukrainians and Romani lived together in a frail but lasting peace. When the II World War began, Polish cities were captured, and one after another citizens were confined to their city in order to keep the public order. In this time of turmoil and uncertainty, one could think that all these cultures, different on their foundations but all composed of human beings that respond in the same way to situations of this nature, would be drawn together, cast aside their differences and try to do what is necessary to ensure the most basic need known to Men, survive. Survival is the most basic instinct of the human race. The fear of not being able to survive generated something that went against this certainty. It generated hate. Not towards the common enemy but from one culture against another. The Nazi German army was ruthless on its march towards dominance but, in some cases, it was not the sole face of terror. The Nazi German army conquered and moved on, leaving governments as a front to keep order. The terror was instilled by others. A true clash of cultures whose aftermath was one of the biggest bloodshed in the history of the civilized world.